2016
DOI: 10.1152/jn.00110.2016
|View full text |Cite
|
Sign up to set email alerts
|

Heat pulse excitability of vestibular hair cells and afferent neurons

Abstract: In the present study we combined electrophysiology with optical heat pulse stimuli to examine thermodynamics of membrane electrical excitability in mammalian vestibular hair cells and afferent neurons. We recorded whole cell currents in mammalian type II vestibular hair cells using an excised preparation (mouse) and action potentials (APs) in afferent neurons in vivo (chinchilla) in response to optical heat pulses applied to the crista (ΔT ≈ 0.25°C per pulse). Afferent spike trains evoked by heat pulse stimuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 78 publications
(115 reference statements)
6
62
1
Order By: Relevance
“…IV E and Ref. [27]), specifically allowing for the PAINTS experiment to estimate a surface charge difference that was found to be in accord with empirical values for neural cells [41].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…IV E and Ref. [27]), specifically allowing for the PAINTS experiment to estimate a surface charge difference that was found to be in accord with empirical values for neural cells [41].…”
Section: Discussionmentioning
confidence: 63%
“…Shapiro et al [16] showed that these rapid temperature variations are directly accompanied by changes in the cell membrane's capacitance and resulting displacement currents which are unrelated to specific ionic channels; their findings on the thermal capacitance increase have been supported by experiments from several additional groups [19,20,[23][24][25]. Shapiro et al [16] also developed a theoretical model where the temperature elevation was seen to give rise to membrane capacitance increase at the membrane's boundary regions (see also Liu et al [26] and Rabbit et al [27]). However, as recently pointed out in our reanalysis of this theoretical model [28,29], upon correcting a mathematical convention error it actually predicts a net capacitance decrease, contrary to the experimental measurements.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Infrared laser pulses have been shown to induce intracellular calcium transients implicating mitochondria in neonatal cardiomyocytes [10] and in neonatal spiral and vestibular ganglion neurons [11] and to depolarize membranes in HEK293 cells [12], dorsal root ganglion neurons [13], oocytes, HEK cells and artificial layers [14], retinal and vestibular primary neurons [15,16], hippocampal neurons [17], spiral ganglion neurons [18], brain slices [19] and in vestibular hair cells and afferent neurons [20]. What remains unclear is whether an universal photothermal mechanism exists and how the transient heating induced by the IR laser pulse elicits membrane depolarization of neurons and action potentials or modulates intracellular signalling.…”
Section: Introductionmentioning
confidence: 99%
“…It has been argued previously that IR heat pulses directly evoke synaptic vesicle release in addition to modulating ion channel conductance and capacitive depolarization (Rajguru et al, 2011;Liu et al, 2014;Rabbitt et al, 2016). Therefore, the expected changes in sensitivity to IR heat pulses after BX administration would be less than the changes in sensitivity to mechanical stimulation.…”
Section: B B B B B B B B B B B B B B B B B B B B B B B B B B B B B mentioning
confidence: 96%